Browning inhibition in in vitro regeneration of Musa Paradisiaca cv. tanduk using ascorbic acid / Mohd Sukri Mohd Nor - Mohd Nor, Mohd Sukri (2020)
Micropropagation of banana is well known and the product derived from it is accepted among banana plantation community. Tissue culture banana basically having better characteristics than banana plant resulting from conventional cultivation. It is due to the plant selection where the plant having much better quality will likely to be choose. With the help of micropropagation technique, it is feasible to produce hundreds to thousands of planting materials with super-trait which is exactly the same as mother plant. In Malaysia, tissue culture technique for several banana cultivar has been established. Unfortunately, it is not for banana known as Tanduk. Problems surrounding tissue culture of Musa paradisiaca cv. Tanduk is mainly due to its high phenolic content which will leads to browning. Unsolved browning issue will cause the death of the plant. In this study, minimization of browning is our concern where micropropagation of Musa paradisiaca cv. Tanduk were subjected with three (3) different treatments: 1) Ascorbic acid 0.0 – 20.0 mg/L; 2) Photoperiod of 16 hours light and 8 hours dark, and 24 hours darkness condition; 3) Half and full medium strength. The result shows that 15.0 mg/L ascorbic acid in a 16 hours light and 8 hours darkness photoperiod were observed to effectively minimize browning in the initiation stage. It is supported by PPO Assay data conducted simultaneously. Finally, variation among the treated banana plants were observed morphologically and the observation conducted shows insignificant variation among the treated banana plants.